Proyecto de factibilidad para la creación de un centro recreacional turístico en el barrio Isimanche, parroquia zumba, cantón Chinchipe, provincia de Zamora Chinchipe, para el año 2016 - Ortega, Cindy Mabel (2017)
The present investment project was carried out to determine the "FEASIBILITY PROJECT FOR THE CREATION OF A TOURISTIC RECREATIONAL CENTER IN THE BARRIO ISIMANCHI, ZUMBA PARK, CANTON CHINCHIPE, PROVINCE OF ZAMORA CHINCHIPE", whose purpose is to carry out a study to visualize the viability to implement this type of company, therefore it is necessary to approach specific objectives such as: market, technical, legal-administrative and financial study. The objective of the current project is to develop a feasibility study for the creation of a Tourist Recreation Center, in Barrio Isimanchi, Zumba Parish; Canton Chinchipe, Province of Zamora Chinchipe, taking advantage of the enormous tourist and cultural biodiversity that owns the same one. For the present investigation we used methods such as: inductive, deductive, statistical and descriptive, we also used the use of research techniques such as: direct observation, survey applied to the families of the Chinchipe canton and the local offer. Thus, the population of the Chinchipe canton was used, amounting to a total of 2,568 families, to which a study sample was determined, giving a sample of 346 surveys to be applied to the families of Chinchipe. In the market study, a potential demand was 2.208, the real demand is 1,833 per use per capita which is 10 gives a total of 18,330, referring to the effective demand of 13,381, and an offer of 2,412, whose difference results in the unsatisfied demand of 10,969. In the technical study the size of the Recreation Center was determined, with an installed capacity of 149,760 services per year and the utilized capacity of 92,477 which represents 95% of the installed capacity for the recreational center. The financial study determined that to start the economic exercise of the proposal requires a total investment of USD 149,557.68 from the United States of America, within the sources of financing there is a credit to the National Finance Corporation whose amount represents the 83% of the total investment represents $ 80,000 with an interest rate of 11.83% for 10 years with semi-annual payments. The total cost of production for the first year is $ 96,977.18 divided value for the annual amount of service that is 142,272 gives the unit cost of $ 0.68 amount that increases a percentage of profit of 55%, obtaining the sale price at public of $ 1.05 value that allows to have a total income of 149,386. Referring to the break-even point for the first year of life of the project is determined by obtaining a total of $ 87,791.93 in revenues and with a capacity of 58.77% of the installed capacity of the recreational center. In addition, net income is $ 31,272.34. The financial economic study showed that the net present value is $ 50,069.31 the internal rate of return is 19.20% higher than the discount rate, the capital recovery period will be 4 years, 5 months and 1 day; the cost-benefit ratio indicates profitability for each dollar invested there is 1.55 of utility and the sensitivity analysis with a 25.63% increase in costs and a 16.55% decrease in revenues do not affect the profitability of the project, both the project is feasible since the initial investment will be recovered. With the environmental impact assessment, it was possible to know that it does not cause negative impacts to the ecosystem, in addition it was determined that they have a positive influence, since it allows a labor stability in the population. In addition, the conclusions and recommendations are presented in accordance with the results achieved in the preparation of the project.